Mali : Request for Modification of Criteria Under the Extended Credit Facility-Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2021)
This staff report proposes the modification of the performance criteria for end-December 2020 for the economic program supported by the three-year Extended Credit Facility (ECF) arrangement that was approved by the Executive Board on August 28, 2019. The modifications aim to accommodate the needed response to combat the COVID-19 pandemic and to adjust the end-December 2020 targets to take account of the impact of the pandemic shock.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Mali